2020
DOI: 10.1101/2020.11.04.369157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Genomes of Bacterial Isolates from Lameness Outbreaks in Broilers

Abstract: We investigated lameness outbreaks at commercial broiler farms in Arkansas. From Bacterial Chondronecrosis with Osteomyelitis (BCO) lesions, we isolated several distinct bacterial species. The results show that BCO-lameness pathogens on particular farms can differ significantly. Genomes for Staphylococcus aureus were highly related to chicken isolates from Europe, but present in the Arkansas area for at least a decade. Phylogenomics suggest that this S. aureus has been restricted to poultry for more than 40 ye… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…We sampled 11 lame birds from that farm and determined that 7 of the birds were infected with S. aureus . Genome analyses showed that the BCO S. aureus isolates were highly related and very closely related to S. aureus isolates obtained from diseased birds or broiler meat dating from 2010 in Oklahoma all the way back to the 1970s in Europe (36, 37). The clade has been identified multiple times in Arkansas and Oklahoma for at least a decade.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We sampled 11 lame birds from that farm and determined that 7 of the birds were infected with S. aureus . Genome analyses showed that the BCO S. aureus isolates were highly related and very closely related to S. aureus isolates obtained from diseased birds or broiler meat dating from 2010 in Oklahoma all the way back to the 1970s in Europe (36, 37). The clade has been identified multiple times in Arkansas and Oklahoma for at least a decade.…”
Section: Discussionmentioning
confidence: 96%
“…Kinky back isolates showed lethality of >70% while cecal isolates showed lethality of <40%. We used E. cecorum 1415 collected from an infected vertebrae in a kinky back bird (36) but it showed no significant lethality (<40%) in the ELA. We compared three E. coli isolates from BCO lame birds (36) and found they had very different apparent virulence in the ELA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations